Antibacterial Activity Ethanolic Extract of Ocimum basilicum L. Leaves in Inhibiting the Growth of Escherichia coli and Pseudomonas aeruginosa - Muhammad Fauzan Lubis; Hafid Syahputra; Ririn Astyka (Nusantara Scientific Medical, 2022)
Infectious disease is the biggest problem in the world. The problem with this infection is related to antibiotic resistance if its use is not consistent. Utilization of kemangi leaves, which are always used as fresh vegetables, has potential as an antibacterial in inhibiting the growth of Escherichia coli and Pseudomonas aeruginosa bacteria. This study aims to analyze the inhibition of an ethanol extract of kemangi leaves against Escherichia coli and Pseudomonas aeruginosa. The Kirby-Bauer method with the disc diffusion method was used to determine the minimum inhibitory diameter and to calculate the activity index value. The test results at a concentration of 500 mg/mL showed activity in the strong category, namely 13.70 ± 0.10 mm (Escherichia coli) and 12.93 ± 0.06 mm (Pseudomonas aeruginosa), and the minimum inhibitory concentration was at a concentration of 3.125 mg/mL. Conclusion the ethanol extract of kemangi leaves shows antibacterial activity.